Early Eocene Ocean Meridional Overturning Circulation: The Roles of Atmospheric Forcing and Strait Geometry. Issue 3 (5th March 2022) - Zhang, Yurui; de Boer, Agatha M.; Lunt, Daniel J.; Hutchinson, David K.; Ross, Phoebe; van de Flierdt, Tina; Sexton, Philip; Coxall, Helen K.; Steinig, Sebastian; Ladant, Jean‐Baptiste; Zhu, Jiang; Donnadieu, Yannick; et al.
Abstract: Here, we compare the ocean overturning circulation of the early Eocene (47–56 Ma) in eight coupled climate model simulations from the Deep‐Time Model Intercomparison Project (DeepMIP) and investigate the causes of the observed inter‐model spread. The most common global meridional overturning circulation (MOC) feature of these simulations is the anticlockwise bottom cell, fed by sinking in the Southern Ocean. In the North Pacific, one model (GFDL) displays strong deepwater formation and one model (CESM) shows weak deepwater formation, while in the Atlantic two models show signs of weak intermediate water formation (MIROC and NorESM). The location of the Southern Ocean deepwater formation sites varies among models and relates to small differences in model geometry of the Southern Ocean gateways. Globally, convection occurs in the basins with smallest local freshwater gain from the atmosphere. The global MOC is insensitive to atmospheric CO2 concentrations from 1× (i.e., 280 ppm) to 3× (840 ppm) pre‐industrial levels. Only two models have simulations with higher CO2 (i.e., CESM and GFDL) and these show divergent responses, with a collapsed and active MOC, respectively, possibly due to differences in spin‐up conditions. Combining the multiple model results with available proxy data on abyssal ocean circulation highlights that strong Southern Hemisphere‐driven overturning is the most likely feature of the early Eocene. In the North Atlantic, unlike the present day, neither model results nor proxy data suggest deepwater formation in the open ocean during the early Eocene, while the evidence for deepwater formation in the North Pacific remains inconclusive. Plain Language Summary: The ocean's overturning circulation refers to the replenishment of the ocean's deep water by cold dense polar surface waters and its eventual return to the surface. It affects the climate through redistribution of heat across the globe and uptake of atmosphere carbon dioxide (CO2 ). Here, we explore the overturning circulation of the Early Eocene, a hot period 47–56 million years ago when atmosphere CO2 levels were similar to the "worst case" projections for the end of this century, in eight climate models setup up for that time. Our results, together with available ocean circulation sediment data for the time, indicate that during the early Eocene deep water originated predominantly from cold surface waters around Antarctica. The North Atlantic source of deep water that today contributes to European's relatively mild climate for its latitude, was completely absent at the time. Interestingly, even when the carbon dioxide in the Eocene model simulations was lowered to levels similar to today and before the industrial revolution, the North Atlantic source of deep water remains absent, indicating that it is the distribution of continents and ice‐sheets, rather than CO2 that is responsible for the difference between the modern and Eocene circulation. Key Points: This study evaluates the ocean's meridional overturning circulation during the early Eocene in eight models of the DeepMIP project The primary region of deep‐water formation depends both on the atmospheric freshwater flux and the strait geometry in the Southern Ocean Compatible with proxy records, six of eight models show that deep waters predominantly originated from the south